Molecular interplay between linc01134 and YY1 dictates hepatocellular carcinoma progression - Rong, Zhonghou (J Exp Clin Cancer Res, 2020)
BACKGROUND: Revealing the mechanical role of long non-coding RNAs (lncRNAs) in tumorigenesis can contribute to novel therapeutic target for cancers. The regulatory role of linc01134 in hepatocellular carcinoma (HCC) has not been studied yet. MATERIALS AND METHODS: qRT-PCR and western blot were conducted to measure relevant RNA and protein expressions. CCK-8, colony formation, EdU, flow cytometry, wound-healing, transwell assays and xenograft experiments were performed to determine the role of linc01134 in HCC. ChIP and luciferase reporter assays were performed to analyze the effects of Yin Yang-1 (YY1) on linc01134 transcription activity. Relevant mechanical experiments were performed to verify interaction between relative genes. RESULTS: YY1 enhanced linc01134 transcription by interacting with linc01134 promoter. Knockdown of linc01134 inhibited proliferation, migration and epithelial-mesenchymal transition (EMT), yet promoting apoptosis in HCC cells. Mechanically, linc01134 acted as miR-324-5p sponge and interacted with insulin-like growth factor 2 mRNA binding protein 1 (IGF2BP1) to increase the stability of YY1 mRNA expression. Up-regulated YY1 continuously stimulated linc01134 expression by enhancing linc01134 promoter activity, forming a positive feedback loop. CONCLUSION: Linc01134/miR-324-5p/IGF2BP1/YY1 feedback loop mediates HCC progression, which possibly provide prognosis and treatment target of HCC.